The Need for Academic Counseling for the 1st Year Students (General Studies Major) at the University of Batna, Algeria - Said Makhloufi (University of Science and Technology, Yemen, 2017)
Abstract: This study aimed to reveal the need for academic counseling by the first year students of general major studies.  The sample consisted of (146) students (65 males and 81 females) at the  university of  Batna, who were accidently selected in the academic year 2014/2015. To achieve the objectives of the study, the researcher adopted the descriptive method, and constructed a questionnaire to investigate the need for academic counseling. After checking the validity and reliability of the research tool, the researcher administered the tool and collected relevant data. Then the data was analyzed on the basis of Pearson correlation coefficient, means, standard deviations, and t-test to identify differences. Besides, the Statistical Package for Social Sciences (SPSS) was used. The study results showed that the first year students of general major studies are in need for academic counseling (psychological needs, study needs and social needs) in the same order. The results also revealed significant differences in the need for academic counseling based on the gender variable  in favor of females who showed a need for the psychological and study counseling, whereas the differences were in favor of males in the social needs.  In light of the research results and findings a set of recommendations and procedures were proposed which will help in guiding and counseling first-year university students.